Civilization in an Islamic perspective - Farooqi, Jamil (International Islamic University Malaysia, 2011)
Civilization is a multidimensional concept used in different connotations and meanings. It signifies the ideological fervor that contours the edifice of a society and shapes the formation of social institutions. It sets up the goals which individuals and society strive to attain and develop different social mechanisms and organizations to that effect. It directs individuals to lead life in a distinct way for a distinct purpose. Civilization in Islamic intellectual ethos is to uphold Allah’s guidance, and establish His order on earth. Islamic civilization is based on the revelatory doctrine underlying the sovereignty and ascendency of Allah (swt) and its manifestation in every walk of individual and social life. It reflects a composite system of life based on the supremacy of Allah (swt), adores human dignity, maintains righteousness and justice and promotes moderation in thought and action.